Control of rapid formation of interchain excited states in sugar-threaded supramolecular wires - Petrozza, A; Brovelli, S; Michels, J; Anderson, H; Friend, R; Silva, C; Cacialli, F (2008)
A study was conducted to demonstrate that threaded molecular wires made of cyclodextrin-insulated conjugated polymers display a significant independence of their fluorescence dynamics from the concentration in aqueous solutions. The study demonstrated that these aqueous solutions were assigned for efficient suppression of interchain species with concentration up to 0.05mg ml -1. It was observed that interchain states are present with increasing concentration in solutions of the uninsulated polymeric analogues, as demonstrated by qualitative and quantitative analysis of their fluorescence decay, which deviate from the exponential decay expected for excitonic species. It was also demonstrated that quantitative analysis of the uninsulated wires isolate the presence of two different time constants, which are assigned to an excitonic decay accelerated by electron transfer to inter-chain species and an excited state.